In vitro digestibility and fermentation kinetics of some north eastern Himalayan tree leaves using cattle rumen fluid as inoculum - CHOUDHARY, SHILPA; SANTRA, ASHOK; SARKAR, SROBANA; DAS, S K (The Indian Journal of Animal Sciences, 2018)
A study was undertaken to evaluate few north eastern Himalayan forest tree leaves [Blemkar (Buddleja asiatica), Phrengpa (Quercus walliasehiana), Maar (Castanopsis indica), Maarma (Spiraea canescens), Domkar (Symplocus racemosa), Matekpa (Quercus fenestrate), Zimbu (Lingustrm myrsinites), Baggar (Berberis aristata) and Ngek sing (Symplocos crataegoides)] for their potential to manipulate rumen fermentation. An in vitro gas production study was conducted for 96 h to obtain the t½ (h) of various leaves. A time dependent increase in gas production was observed for all tree leaves during 96 h incubation period. The rate constant of gas production (c) was highest for Phrengpa and Ngek sing leaves. IVTDMD (%) and TVFA (mM/dl) at t½ (h) was highest for Zimbu, Maarma and Ngek sing tree leaves. Moreover, microbial biomass production (MBP) per unit digested dry matter was highest for Maar followed by Phrengpa and Maarma leaves at t½ (h). Therefore, from the present study, it can be inferred that these tree leaves can influence in vitro rumen fermentation positively and might serve as newer feed resource for livestock.